Eksplorasi dan uji patogenisitas jamur entomopatogen di PTPN VII Unit Bunga Mayang sebagai pengendali hayati hama penggerek batang tebu (Chilo sacchariphagus) - Eva Rahmawati; Rosma Hasibuan; Yuyun Fitriana; Lestari Wibowo (Jurnal Proteksi Agrikultura, 2026)
This research aims to obtain entomopathogenic fungal isolates and determine the characteristics of isolates that have the potential as biological control agents for Chilo sacchariphagus. The research was conducted in the field and at the Protection Laboratory of PT Perkebunan Nusantara VII Bunga Mayang Unit and at the Biotechnology Laboratory of the Faculty of Agriculture, University of Lampung. This research method consists of two sub-sections; the first is the exploration of entomopathogenic fungi, the second is the morphological identification of entomopathogenic fungal isolates isolated from soil suspensions and bait insects and characteristic tests consisting of growth, sporulation, viability and pathogenicity tests against C. sacchariphagus in vitro arranged in a randomized block design (RBD). From the results of the research, six fungal isolates were obtained, two isolates was able to be identified, as Trichoderma sp., and as Aspergillus sp., while the other four isolates could not be identified. Based on the growth, sporulation, spore viability, and pathogenicity tests against C. sacchariphagus that have been carried out, the six isolates have varying characteristics. The TC (Trichoderma sp.) isolate had the highest fungal colony growth, which was 8,50 cm in diameter, the highest sporulation (3,96 x 107 spores/mL) was TNH3BB isolate, and the highest spore viability (100%) were belong the TNH3BB and TC (Trichoderma sp.) isolates, while the TNH2BA (Aspergillus sp.) isolate was able to cause the highest mortality to up, 93,33%.